THE EFFECTIVENESS OF DEVELOPMENTAL PRE-SCREENING QUESTIONNAIRE MONITOR BOOK IN INCREASING KNOWLEDGE : QUASI PRE EXPERIMENTAL - Ni Nyoman Ayuk Widiani; Made Pradnyawati Chania (Universitas Karya Husada Semarang, 2025)
Child development monitoring is very important. The prevalence of developmental delays in children under 5 years of age in Indonesia in 2018 was reported by WHO as 7,512.6 per 100,000 population (7.51%). The purpose of this study was to determine the effectiveness of the Developmental Pre-Screening Questionnaire (DPSQ) monitoring book in increasing caregivers' knowledge in conducting early detection of early childhood development. This study was a quasi-pre-experimental study with a one-group pretest and posttest design. The sample in this study were all caregivers at the Metta Mama &Maggha Foundation. The results of the study showed that the average level of caregiver knowledge in conducting Early Detection of Early Childhood Development before being given the DPSQ monitoring book was 74.81. The average level of knowledge of caregivers in conducting Early Detection of Early Childhood Development after being given the DPSQ monitoring book was 95.19 (p value = 0.000). From the results of this study, it is expected that caregivers can carry out early detection of development with the DPSQ so if there is a developmental delay, appropriate handling can be carried out.